2017
DOI: 10.1002/cssc.201700153
|View full text |Cite
|
Sign up to set email alerts
|

MechanoAPI‐ILs: Pharmaceutical Ionic Liquids Obtained through Mechanochemical Synthesis

Abstract: An alternative, efficient, and green synthetic strategy for the preparation of pharmaceutical ionic liquids using mechanochemistry (MechanoAPI-ILs) is reported. Six new API-ILs based on gabapentin and l-glutamic acid were successfully synthesized and characterized, demonstrating that mechanochemistry is a very promising synthetic strategy. Results compare both the new and the classical approach and clearly show the advantages of the new method. This new technique is faster, solvent free, reproducible, selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…10 This technique eliminates the need for large volumes of solvents and lengthy conventional solution syntheses and it has been demonstrated that the products prepared via mechanochemistry are obtained in higher yields, without solvent residues and in a shorter time span. 11 Over the years, ILs became renown as sustainable and green materials. 12,13 Reactivity in crystals depends on a balance between steric packing factors and electronic properties and the fundamental problem is how the two processes are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…10 This technique eliminates the need for large volumes of solvents and lengthy conventional solution syntheses and it has been demonstrated that the products prepared via mechanochemistry are obtained in higher yields, without solvent residues and in a shorter time span. 11 Over the years, ILs became renown as sustainable and green materials. 12,13 Reactivity in crystals depends on a balance between steric packing factors and electronic properties and the fundamental problem is how the two processes are interrelated.…”
Section: Introductionmentioning
confidence: 99%
“…We synthesized four new ionic liquids containing gabapentin, both as an anion and as a cation, which we called mechanoAPI-ILs (Active Pharmaceutical Ingredient-Ionic Pursuing our studies with gabapentin and our work with polymorphism, again using mechanochemistry, we decided to check if we could avoid gabapentin polymorphism by using it as a liquid instead of a solid. We synthesized four new ionic liquids containing gabapentin, both as an anion and as a cation, which we called mechanoAPI-ILs (Active Pharmaceutical Ingredient-Ionic Liquids obtained mechanochemically) [46].…”
Section: Novel Multicomponent Crystal Forms and Ionic Liquidsmentioning
confidence: 99%
“…Table 2. Physical state, yield, thermal properties (T g ), and reaction time obtained for all compounds in each synthetic method [46].…”
Section: Novel Multicomponent Crystal Forms and Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been an area of growing interest in Portugal, with several research groups devoting their efforts towards the design and synthesis of solvates, salts, and cocrystals. More recently, the synthesis of pharmaceutical ionic liquids via these methods has also been reported as possible [ 35 ].…”
Section: Introductionmentioning
confidence: 99%